2020
DOI: 10.5812/jjm.100348
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of qnr and aac(6’)Ib-cr Genes Among ESBL-Producing Klebsiella pneumoniae Strains Isolated from Burn Patients in Kermanshah, Iran

Abstract: Background: Assessment of bacteria such as Klebsiella pneumonia has shown that Plasmid-mediated quinolone resistance (PMQR) affects antibiotics resistance (e.g., quinolones). Objectives: We studied the prevalence of qnr and aac(6’)Ib-cr genes in extended-spectrum beta-lactamase (ESBL)-producing K. pneumonia strains isolated from burn wounds of patients in the city of Kermanshah, Iran. Methods: This descriptive-analytical study was conducted on 126 K. pneumonia strains isolated collected from burn wounds. Bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
0
6
2
Order By: Relevance
“…Instead, consistent with Ruppe et al [ 33 ], the BC9_TM strain was found to possess the aac(6′)-Ib-cr5 gene but without phenotypic expression of amikacin resistance. Vaziri et al underscored the fundamental role of the qnrB gene in the K. pneumoniae genome, which, in association with the aac(6′)-Ib-cr5 gene, contributes to increased resistance to aminoglycosides, fluoroquinolones, and cephalosporins [ 36 ], a conclusion that was not supported by our findings. A recent nationwide epidemiological survey conducted in Greece confirmed a divergence between the resistance phenotype and the AME genotype for aminoglycosides, probably as a consequence of various competing resistance mechanisms associated with the distinct catalytic activities of AME genes [ 37 ].…”
Section: Discussioncontrasting
confidence: 71%
“…Instead, consistent with Ruppe et al [ 33 ], the BC9_TM strain was found to possess the aac(6′)-Ib-cr5 gene but without phenotypic expression of amikacin resistance. Vaziri et al underscored the fundamental role of the qnrB gene in the K. pneumoniae genome, which, in association with the aac(6′)-Ib-cr5 gene, contributes to increased resistance to aminoglycosides, fluoroquinolones, and cephalosporins [ 36 ], a conclusion that was not supported by our findings. A recent nationwide epidemiological survey conducted in Greece confirmed a divergence between the resistance phenotype and the AME genotype for aminoglycosides, probably as a consequence of various competing resistance mechanisms associated with the distinct catalytic activities of AME genes [ 37 ].…”
Section: Discussioncontrasting
confidence: 71%
“…Frequencies of oqxA and B genes found in this study are higher than those reported by Azargun in Tabriz, Iran in 2018 which were 33.7 for oqxA and 20.6% for oqxB [9]. Previous studies have found that the prevalence of PMQR genes is more common in ESBL-producing K. pneumoniae [4,9,20]. We found that PMQR genes (aac(6′)-Ib-cr, qnrS, qnrB) were also be detected in strains containing ESBL determinants.…”
Section: Discussioncontrasting
confidence: 63%
“…CTX-M-15type ESBL-producing strains have especially increased in recent years [5][6][7]. Presence of PMQR determinants including qnr genes, aac (6')-Ib-cr, and e ux pumps genes qepA, qepA2, and oqxAB confer reduced susceptibility to uoroquinolones and facilitate selection of uoroquinolone resistance in K. pneumoniae [4,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Klebsiella pneumoniae is one of the pioneer pathogens in causing a wide range of nosocomial and community‐acquired infections, including septicemia, pneumonia, meningitis, soft tissue infections, and urinary tract infections 1,2 . Global concerns about this pathogen are growing due to the increased incidence of resistance to quinolones and other classes of antibiotics, as well as the declining effectiveness of treating infections 3,4 .…”
Section: Introductionmentioning
confidence: 99%